Postpartum depression in Malaysian women: the association with the timing of pregnancy and sense of personal control during childbirth - Mohd Arifin, Siti Roshaidai; Ahmad, Aini; Abdul Rahman, Rasnah; Huai, Seng Loh; Chong, Guan Ng (2014)
ABSTRACT Objective: To determine the prevalence of postpartum depression (PPD) in Malaysian women and its association with unplanned pregnancy and experience of control during childbirth. Methods: A cross-sectional study involving women 24-48 hours after delivery. PPD was measured with the Edinburgh Postpartum Depression Scale and the timing of pregnancy was assessed with a four question scale. Sense of personal control during childbirth was measured with the Labour Agentry Scale. Other relevant clinical and demographic data were collected. Results: Of the 347 women included, the prevalence of PPD was 31.7%. There were higher risks in women with unplanned pregnancies [45% vs. 26.3%; χ2 = 11.477, df = 1 p < 0.01]. Lower score of childbirth control was associated with PPD [CI 7.23-13.96, p < 0.01]. Conclusion: Screening for women with unplanned pregnancies and education for those with low sense of control during childbirth help to reduce the risk of PPD.